SIKAP PENGELOLA KEUANGAN DAN PERILAKU PERENCANAAN INVESTASI KELUARGA DI SURABAYA - Meliza Silvy; Norma Yulianti (Journal of Business & Banking, 2013)
Being lack and ignorant of family financial management knowledge generally is due to being lack of investment and planning for the welfare of the family. The lack of such knowledge can lead to financial decisions every day. Therefore, experience in managing finance is neces- sary. Individual experiences is a learning process in managing financial and investment planning so that in making financial decisions every day can be focused and wiser. This study focuses on financial knowledge and experience as a measure of literacy that influences the attitudes and behavior of family financial investment planning in Surabaya. This study used questionnaires which were distributed to 380 respondents. The sampling method was pur- posive sampling, based on family income with a minimum income of Rp 2,000,000 per month. The results showed that knowledge in finance and financial experience affect the investment behavior of family financial planning, financial management attitudes moderating influence and strengthen the financial knowledge and experience does not moderate influence on the behavior of financial investment planning family finances.